Single-channel recordings of three K+-selective currents in cultured chick ciliary ganglion neurons - Gardner, PI (J Neurosci, 1986)
Multiple distinct K+-selective channels may contribute to action potential repolarization and afterpotential generation in chick ciliary neurons. The channel types are difficult to distinguish by traditional voltage-clamp methods, primarily because of coactivation during depolarization. I have used the extracellular patch-clamp technique to resolve single-channel K+ currents in cultured chick ciliary ganglion (CG) neurons. Three unit currents selective for K+ ions were observed. The channels varied with respect to unit conductance, sensitivity to Ca2+ ions and voltage, and steady-state gating parameters. The first channel, GK1, was characterized by a unit conductance of 14 pico- Siemens (pS) under physiological recording conditions, gating that was relatively independent of membrane potential and intracellular Ca2+ ions, and single-component open-time distributions with time constants of approximately 9 msec. The second channel, GK2, was characterized by a unit conductance of 64 pS under physiological recording conditions and gating that was affected by membrane potential but was not dependent on the activity of intracellular Ca2+ ions. Open-time distributions indicated 2 open states, with open-time constants of 0.09 (61%) and 0.35 (39%) msec, at +40 mV membrane potential. The third channel, GKCa2+, was identified in isolated patch recordings in which the concentration of internal Ca2+ was 10(-7) M or greater, which was an absolute prerequisite for channel opening. GKCa2+ was characterized by a unit conductance of 193 pS in symmetrical 0.15 M KCl solutions, an open-state probability that was a function not only of [Ca2+]i, but also of membrane potential, and single-component open-time distribution with a time constant of 1.11 msec at -10 mV patch potential. These results suggest the presence of at least 3 distinct K+ channel populations in the membrane of cultured chick CG neurons.